1996
DOI: 10.1063/1.472018
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and dynamics of the initial dissociative chemisorption of oxygen on Ru(001)

Abstract: We have used supersonic molecular beam techniques to measure the initial dissociative chemisorption probability S 0 of O 2 on Ru͑001͒ as a function of incident kinetic energy E i , surface temperature T s , and angle of incidence i . We observe different behavior in the adsorption dynamics in two separate kinetic energy regimes: the value of S 0 decreases with incident energy in the low kinetic energy regime, and the value increases with incident energy in a higher kinetic energy regime. In the low energy regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 45 publications
5
66
0
Order By: Relevance
“…3, our results for clean Ru(0001) are in very good agreement with the data taken from Ref. 30, which were obtained at a surface temperature of 500 K and normal incidence (normal energy scaling has been also verified in Ref. 30).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…3, our results for clean Ru(0001) are in very good agreement with the data taken from Ref. 30, which were obtained at a surface temperature of 500 K and normal incidence (normal energy scaling has been also verified in Ref. 30).…”
Section: Resultssupporting
confidence: 81%
“…The crystal temperature is 300 K, and the angle of incidence is i = 15 • . The data reported by Wheeler et al 30 for Ru(0001) under similar incident conditions are also shown. For 1 ML Cu and 2 ML Cu, we observe a monotonic increase of the initial sticking probability with incident beam energy, with progressively reduced values as the thickness of the layer increases and for energies lower than 200 meV.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…[11][12][13] Here we present experimental evidence with supporting density functional theory (DFT) calculations of carbonate formation and decomposition from the adsorption of oxygen-labeled carbon dioxide (C 18 O 2 ) on an atomic oxygen ( 16 O) precovered Au(111) surface. We studied the effects of CO 2 exposure, surface temperature, and oxygen coverage on carbonate formation and decomposition and also estimated reaction probabilities (∼10 -3 -10 -4 ) and activation energies as a function of conditions.Our experiments were performed in a UHV chamber that has been described elsewhere, [14][15][16][17][18][19] but details specific to this study are briefly summarized here. The Au(111) single crystal sample is mounted to a tantalum plate that can be resistively heated and is in thermal contact with a liquid nitrogen bath.…”
mentioning
confidence: 99%
“…212,218 In the case of adsorption of O2 on Ru, which undergoes via a limited precursormediated dissociative chemisorption, there are several studies on kinetics of O2 adsorption on monocrystalline Ru. 215,216,219,220,221 However, to the best of our knowledge, there is no reported data for oxygen adsorption kinetics on polycrystalline Ru at room temperature. Polycrystalline Ru is relevant due to that the structure of Ru thin films used as oxidation resistant protective layers for DRAMs, CMOS devices, solar cells, or EUVL optics is either polycrystalline or amorphous rather than monocrystalline.…”
Section: Introductionmentioning
confidence: 99%